OUTCOME OF DEVELOPMENTAL THERAPY IN CHILDREN WITH CEREBRAL PALSY CHILDREN: A PROSPECTIVE COHORT - Afzal, Erum; Ahmad, Tanveer; Iqbal, Muhammad Khalid; Aftab, Kausar; Muein, Rubeena (Journal of Rawalpindi Medical College, 2023)
Introduction: Cerebral palsy (CP) is the non-progressive disorder of motor and posture with associated delayed development in areas of cognition, perception, behavior and sensation, due to insult to immature brain. Improvement in all developmental domains of CP patients depends upon early institution of rehabilitation programs involving all multidisciplinary approach. The portage early education program (PEEP) is a worldwide, effective and early interventional method, for developmentally delayed children. Objective: To determine the outcome of developmental therapy in children with CP by using PEEP. Study Design: Experimental research design (within group) Settings: The children hospital and the institute of child health Multan. Methodology: 156 patients of 2 to 10 years of age, both gender from January 2020 to December 2020, diagnosed as CP were enrolled for this study. All children were assessed by using PEEP and GMFM (Gross Motor Function Measure) twice 6 months apart. A trained clinical psychologist administered PEEP to all the children. All the Patients were advised regular weekly sessions at hospital by multidisciplinary team and at least 2 hours per day for continuation of these therapies at home. At the end of 6 months we found that all families had not followed this. The patient who visited >2times/month were considered compliant and those visited <2times/month were considered non-compliant. Data was analyzed by using SSPS version 16. Paired t test was used to compare the developmental outcome of compliant and non-compliant groups. Results: Out of 156 participants, 58(37%) were in compliant and 98(63%) non-compliant. Male subjects were prominent 42(72.41%) and 67(68.37%) respectively. Most of the participants belonged to 3-6 years of age in both groups28(48.29%) and 51(52.04%) respectively. Spastic quadriplegia (26(44.83%), 57 (58.16%)), and level 5 on GMFM 24(42.86) and 52(53.06%) respectively was commonly presents in both patient groups. The mean comparison of DQ of Compliant CP Children at initial stage and after six months in areas of GM, C, SH, S, L and GMFM was found statistically significant. Conclusion: CP children should be on regular follow up for developmental therapy for long time for better outcome. PEEP is an excellent system for the assessment, training and rehabilitation of children with delayed development.